Solve for t
t = \frac{\sqrt{345} + 35}{16} \approx 3.348385976
t = \frac{35 - \sqrt{345}}{16} \approx 1.026614024
Share
Copied to clipboard
-16t^{2}+70t+5=60
Swap sides so that all variable terms are on the left hand side.
-16t^{2}+70t+5-60=0
Subtract 60 from both sides.
-16t^{2}+70t-55=0
Subtract 60 from 5 to get -55.
t=\frac{-70±\sqrt{70^{2}-4\left(-16\right)\left(-55\right)}}{2\left(-16\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -16 for a, 70 for b, and -55 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
t=\frac{-70±\sqrt{4900-4\left(-16\right)\left(-55\right)}}{2\left(-16\right)}
Square 70.
t=\frac{-70±\sqrt{4900+64\left(-55\right)}}{2\left(-16\right)}
Multiply -4 times -16.
t=\frac{-70±\sqrt{4900-3520}}{2\left(-16\right)}
Multiply 64 times -55.
t=\frac{-70±\sqrt{1380}}{2\left(-16\right)}
Add 4900 to -3520.
t=\frac{-70±2\sqrt{345}}{2\left(-16\right)}
Take the square root of 1380.
t=\frac{-70±2\sqrt{345}}{-32}
Multiply 2 times -16.
t=\frac{2\sqrt{345}-70}{-32}
Now solve the equation t=\frac{-70±2\sqrt{345}}{-32} when ± is plus. Add -70 to 2\sqrt{345}.
t=\frac{35-\sqrt{345}}{16}
Divide -70+2\sqrt{345} by -32.
t=\frac{-2\sqrt{345}-70}{-32}
Now solve the equation t=\frac{-70±2\sqrt{345}}{-32} when ± is minus. Subtract 2\sqrt{345} from -70.
t=\frac{\sqrt{345}+35}{16}
Divide -70-2\sqrt{345} by -32.
t=\frac{35-\sqrt{345}}{16} t=\frac{\sqrt{345}+35}{16}
The equation is now solved.
-16t^{2}+70t+5=60
Swap sides so that all variable terms are on the left hand side.
-16t^{2}+70t=60-5
Subtract 5 from both sides.
-16t^{2}+70t=55
Subtract 5 from 60 to get 55.
\frac{-16t^{2}+70t}{-16}=\frac{55}{-16}
Divide both sides by -16.
t^{2}+\frac{70}{-16}t=\frac{55}{-16}
Dividing by -16 undoes the multiplication by -16.
t^{2}-\frac{35}{8}t=\frac{55}{-16}
Reduce the fraction \frac{70}{-16} to lowest terms by extracting and canceling out 2.
t^{2}-\frac{35}{8}t=-\frac{55}{16}
Divide 55 by -16.
t^{2}-\frac{35}{8}t+\left(-\frac{35}{16}\right)^{2}=-\frac{55}{16}+\left(-\frac{35}{16}\right)^{2}
Divide -\frac{35}{8}, the coefficient of the x term, by 2 to get -\frac{35}{16}. Then add the square of -\frac{35}{16} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
t^{2}-\frac{35}{8}t+\frac{1225}{256}=-\frac{55}{16}+\frac{1225}{256}
Square -\frac{35}{16} by squaring both the numerator and the denominator of the fraction.
t^{2}-\frac{35}{8}t+\frac{1225}{256}=\frac{345}{256}
Add -\frac{55}{16} to \frac{1225}{256} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(t-\frac{35}{16}\right)^{2}=\frac{345}{256}
Factor t^{2}-\frac{35}{8}t+\frac{1225}{256}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(t-\frac{35}{16}\right)^{2}}=\sqrt{\frac{345}{256}}
Take the square root of both sides of the equation.
t-\frac{35}{16}=\frac{\sqrt{345}}{16} t-\frac{35}{16}=-\frac{\sqrt{345}}{16}
Simplify.
t=\frac{\sqrt{345}+35}{16} t=\frac{35-\sqrt{345}}{16}
Add \frac{35}{16} to both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}